Effects of slide-board-based high-intensity interval versus moderate-intensity continuous training on aerobic and anaerobic capacity in young speed skaters - Kai Zhang; Jing Qi; Peng Shi; Xin Xue; Yuanguo Liu (PLoS ONE, 2026)
Purpose This study aimed to compare the effects of three slide-board training modalities—two high-intensity interval training protocols (HIIT1: 3 min work/2 min rest; HIIT2: 4 min work/1 min rest) and one moderate-intensity continuous training protocol (MICT: 20 min at 70% HRmax)—on aerobic and anaerobic capacities in young speed skaters. Methods Twenty-seven youth speed skaters (15 males, 12 females) were randomly assigned to HIIT1, HIIT2, or MICT groups (n = 9 each). All participants completed a 4-week intervention (3 sessions/week) using a slide-board simulator. Aerobic capacity was assessed via maximal oxygen uptake (VO2max) and peak aerobic power output (Pmax) using an incremental cycle test. Anaerobic performance was evaluated with a 30-second Wingate test, including relative peak power (RPP), relative mean power (RMP), and fatigue index (FI). Pre- and post-test data were analyzed using two-way repeated measures ANOVA and paired t-tests. Results Both HIIT1 and HIIT2 significantly improved VO2max, RPP, and RMP, and reduced FI (p < 0.05), whereas MICT showed no significant changes in any variable. HIIT2 demonstrated greater improvements in Pmax and anaerobic power metrics compared to HIIT1, though intergroup differences were not statistically significant. HIIT1 appeared to enhance fatigue resistance more effectively. Conclusion Slide-board HIIT is an effective short-term training method for enhancing aerobic fitness and anaerobic power in youth speed skaters. HIIT2 (4 + 1 structure) may be more beneficial for sprinters requiring explosive power, while HIIT1 (3 + 2 structure) may suit middle- to long-distance skaters focusing on endurance and fatigue resistance. MICT alone appears insufficient to induce meaningful physiological adaptations in a 4-week period. These findings support the use of structure-specific HIIT protocols for sport-specific conditioning in speed skating.